Preventing Staphylococcus aureus stainless steel‐associated infections in orthopedics. A systematic review and meta‐analysis of animal literature. Issue 12 (26th March 2021) - Tsikopoulos, Konstantinos; Sidiropoulos, Konstantinos; Kitridis, Dimitrios; Moulder, Elizabeth; Ahmadi, Milad; Drago, Lorenzo; Lavalette, David
Abstract: Surgical site infection in the presence of orthopedic implants poses significant healthcare and socioeconomic burden. To assess the potential of various prevention strategies against Staphylococcus ‐induced stainless steel‐associated infections, a review of animal evidence was designed. The databases of PubMed, Embase, and CENTRAL were searched until March 10, 2020, for articles including animal models with stainless steel instrumentation and techniques to prevent Staphylococcus infection. We conducted a random‐effects meta‐analysis of standardized mean differences (SMD) with subgroup analysis linked to various protection strategies and we recorded complications. Quality was assessed with the SYRCLE's risk of bias tool. Twenty‐five studies were included. Combined active coating (featuring organic antibacterial compound release) and degradable passive finishing (lipid‐ or polymer‐based structure modification reducing bacterial adhesion) was favored over untreated controls (SMDs for methicillin‐sensitive Staphylococcus aureus [MSSA] and methicillin‐resistant Staphylococcus aureus [MRSA] were −3.46, 95% CI [−4.53 to −2.4], p  < .001 [ n  = 4 head‐to‐head comparisons]; and −6.67, 95% CI [−10.53 to −3], p  < .001 [ n  = 5 head‐to‐head comparisons], respectively). Systemic vitamin D supplementation and systemic antibiotic administration with or without local antibiotics demonstrated favorable outcomes against MSSA infection. On the contrary, no benefit was seen following vaccination. Of note, no side effects were documented. On the basis of data gathered from eight studies, which comprised 294 animals, a bioresorbable polymer‐ or lipid‐based surface modification supplemented with organic coating yielded improved infection‐related outcomes against MSSA and MRSA stainless steel infections, and therefore, this strategy could be further investigated in human research.